(untitled) (Global Journal of Management and Business Research, 2019)
This research is part of the process of adopting innovations in public organizations. It tries to understand how the quality approach implements a hybridization between mechanistic logic and organic logic. Interviews and a literature review examine this issue through four ISO 9001 certifications in a public hospital of last resort. The theory of the network actor is mobilized to infer interpretations. The results show the presence of a mechanical logic based on the application of the precepts of quality. Organic logic, on the other hand, begins with the ability to bridge incompatibilities and build the branch’s trust network. Hybridization is a dynamic device linking the project, sponsor, process, feedback, ecosystem and environment.